Web user interface: local websites versus users’ mental model pattern for Asean. - Aslina Baharum; Azizah Jaafar (Asian Research Publishing Network, 2015)
Even though there is a great development of mobile application nowadays, a web-based platform is still the necessary development for accessing information. The web interface is an important part of a web structure or web layout of a website which captures the users’ eyes at first glance, whether it is appealing and expected or not. Do the developers or designers develop the web user interface (UI) based on users’ mental model pattern (uMMp)? Or do they realize that experienced and knowledgeable users may have an expected look of the layout or in particular, the localization of the web objects? Every user may have different expectations of the same website, but it may be significantly different when compared to users from other countries. This study will compare and identify the ASEAN uMMp UI with the UI of popular websites in the Association of Southeast Asian Nations (ASEAN). The aim of the study is to prove that the users may have created their own mental model pattern when looking at a website. This result can hopefully inspire other designers or researchers of the usefulness of web development based on uMMp for web design development improvement in the future.